Sexual Reproduction of Setosphaeria turcica in Natural Corn Fields in Thailand - Bunkoed, Warapon; Kasam, Supot; Chaijuckam, Patcharavipa; Yhamsoongnern, Jeeranan; Prathuangwong, Sutruedee (Agriculture and Natural Resources, 2014)
Setosphaeria turcica, a teleomorph of Exserohilum turcicum, is the casual agent of northern corn leaf blight, a major disease of corn in Thailand. It is a heterothallic fungus, with two mating types: mating type A and mating type a. This study was the first to investigate the sexual reproduction of S. turcica in Thailand. Pseudothecia (sexual state) were found on heavily infected corn leaves from natural fields, even though until this time, the sexual state has not yet been discovered in the natural world. S. turcica isolates collected from nine corn fields were capable of sexual reproduction in culture when opposite mating types were paired, regardless of the origin of the isolates. Pseudothecia, asci and ascospores could be induced on potato dextrose agar and on Sach’s agar at 23oC and 25-30oC. This study designed mating type-specific primers for both mating types and identified mating type of 225 S. turcica isolates. The result revealed near mating type equilibrium in that 104 and 121 isolates were mating type A and mating type a, respectively. Both mating types were present in every field population. The data suggested that sexual reproduction of S. turcica may be common in corn fields in Thailand and has caused genetic variation in the fungal pathogen, supported by previous analysis with inter-simple sequence repeat markers. Furthermore, the virulence may be enhanced or new physiological races may be generated through sexual hybridization.